Recurrent acute otitis media: a survey of current management in England. Issue 10 (3rd October 2021) - Hampton, T; Whitehall, E; Beasley, C; Stevens, K; Lowe, N; Hogg, E; Bhat, J; Emerson, H; Krishnan, M; Sharma, S
Abstract: Objective: Recurrent acute otitis media is common in children. The preferred treatment measures for recurrent acute otitis media have a mixed evidence base. This study sought to assess baseline practice across ENT departments in England. Methods: A national telephone survey of healthcare staff was conducted. Every ENT centre in England was contacted. A telephone script was used to ask about antibiotic and grommet use and duration in recurrent acute otitis media cases. Results: Ninety-six centres (74 per cent) provided complete information. Recurrent acute otitis media treatment across England by ENT departments varied. The antibiotic first- and second-line prophylaxis offered varies, with trimethoprim used in 33 centres and 29 centres not offering any antibiotics. The timing or choice about when to use grommets also varies, but 87 centres (91 per cent) offer grommet surgery at one stage. Conclusion: The treatments received by children in England for recurrent acute otitis media vary by centre; collaborative research in this area is advised.